Employee wellbeing and cost reduction drivers of corporate social responsibility: Evidence from Congolese mining sector - Sun, Huaping; Bahizire, Grace Mulindwa (Frontiers in Psychology, 2023)
This research investigated the organizational motivation for implementing Corporate Social Responsibility (CSR) based on the perspective of the managers in the mining sector of the Democratic Republic of Congo (DRC). The empirical study was carried on a sample of 103 firms, the study utilized LISREL for a structural equation modeling. The wellbeing of employee and cost reduction were identified as the internal driving factors towards Corporate Social Responsibility. As established, from the managerial perspective, the findings of this study reveal that; firstly, the firm’s pursuit for cost reduction is a positive predictor to CSR implementation; secondly, firms are driven to CSR in order to ensure the wellbeing of their employees, fostered by compliance with the labor standards in the mining sector. Whereof, CSR compliance was included as a mediating variable. Lastly, the lack of resource remains a barrier to CSR implementation. This research responds to the deficient of novelty and lack of academic studies on the drivers of CSR in the mining sector in the sub Saharan regions.